Comparative studies of callus induction and plant regeneration from mature embryos in rice mutants (Journal of the Bangladesh Agricultural University, 2010)
Experiments were performed with mature embryos of four rice mutants for in vitro callus induction and plant regeneration. Different concentrations of 2,4-D and BAP combined, Kn and NAA combined and MET were used to assess their effects on induction of callus, shoot and roots. Given concentrations of 2,4-D with BAP and rice mutants in vitro cultures showed that Y-1281 and Atomita-4 had produced the highest percentages of callus at 2 mgl-1 2,4-D with 0.5 mgl-1 BAP in both light and dark conditions. Similar results were obtained in terms of concentrations and genotypes when 2,4-D and BAP were used together. Combined 2,4-D and BAP treatments showed significantly higher callusing under light conditions (90%). For shoot and root regenerations, once again the mutant genotype Y-1281 produced the highest percentages of shoots and roots and it also showed highest root length. And 11 mgl-1 2,4-D, 0.5 mgl-1 NAA combined and 2.5 mgl-1 MET concentration resulted significantly the highest shoot and root regeneration. Keywords: Callus induction; Mature embryos; Plant regeneration; Root induction; Rice DOI: 10.3329/jbau.v7i1.4796 J. Bangladesh Agril. Univ. 7(1): 39-45, 2009